L’approche communicationnelle en études du jeu : un apport des chercheur.se.s de la Faculté de communication de l’UQAM - Maude Bonenfant; Gabrielle Trépanier-Jobin; Laura Iseut Lafrance St-Martin (Communiquer)
Game studies have recently been developed by researchers from different disciplines, each with their own concepts, approaches and methodologies. This article describes how researchers in game studies from the Faculty of Communication of the Université du Québec à Montréal (UQAM) have contributed to the institutionalization of this area of research in the Francophonie, as well as to the development of a conceptual, epistemological and methodological framework specific to the study of games in the field of communication. After having situated their work in the constellation of researches about games, this article will present the postulates of their communication approach, the different types of communication that can be studied in this domain, as well as the levels of analysis corresponding to potential fields where studies about games can be conducted.